Against knowledge closure - Alspector-Kelly, Marc (Cambridge : Cambridge University Press, 2021)
Against Knowledge Closure" by Marc Alspector-Kelly delves into the fundamental epistemological principle of knowledge closure, which asserts that if one knows something and recognizes its logical implications, then one also knows those implications. The book presents a compelling argument against this principle, challenging its validity across various epistemological theories. Unlike previous critiques, Alspector-Kelly's approach is non-partisan, avoiding reliance on specific epistemological frameworks. By examining a wide range of epistemological concepts, including skepticism, warrant, and fallibilism, he offers a comprehensive analysis of the limitations of knowledge closure. The book is valuable for both seasoned epistemologists and those new to the field, providing a thought-provoking exploration of this central epistemic principle.
Includes bibliographical references (p. 233-241) and index.
Keywords: Knowledge closure; Arguments against knowledge closure; Epistemological theories and closure